The smooth dependence of the solution of the Neumann boundary-value "cell" problem on the parameters of a domain - Khilkova, L.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
The smooth dependence of the solution of the Neumann boundary-value "cell" problem for the Poisson equation on the parameters of a domain is proved by methods of the periodic potential theory.